Unravelling the unseen threat of polyhydramnios in patients with gestational diabetes mellitus: a case report - A Wahab, Syamimi Nadiah; Said, Abdul Hadi; Wan Ismail, Wan Hasmawati (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association of Malaysia, 2023)
Polyhydramnios is dened as an increase in the amount of amniotic uid during pregnancy. is article presents the case of a 35-year-old G4P3 lady at 28 weeks of gestation with suboptimised gestational diabetes Mellitus (GDM). Routine transabdominal ultrasound showed the presence of polyhydramnios, initially thought to be due to suboptimal glucose control. Further evaluation revealed a congenital diaphragmatic hernia with multiple soft markers. Identifying the underlying causes of polyhydramnios can be challenging in primary care settings, which can be attributed to various factors. Although primary care medical ocers may not be required to perform detailed scans, they have a crucial role in identifying gross foetal abnormalities. is study highlights the potential for missed diagnoses in primary care settings and the importance of comprehensive prenatal assessments to ensure early detection and appropriate management of polyhydramniosrelated conditions in women with GDM.